2019
DOI: 10.1002/adfm.201901370
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile Approach for Direct Patterning of Liquid Metal Using Magnetic Field

Abstract: Patterning of liquid metal (LM) is usually an integral step toward its practical applications. However, the high surface tension along with surface oxide makes direct patterning of LM very challenging. Existing LM patterning techniques are designed for limited types of planar substrates, which require multiple-step operation, delicate molds and masks, and expensive equipment. In this work, a simple, versatile, and equipment-free approach for direct patterning of LM on various substrates using magnetic field is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
130
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(143 citation statements)
references
References 71 publications
0
130
0
Order By: Relevance
“…Directly writing [36,77,79] Injection [40] Selective plating [90,91] Magnetic field patterning [92] Electric field patterning [95] Laser patterning [68] Resolution…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Directly writing [36,77,79] Injection [40] Selective plating [90,91] Magnetic field patterning [92] Electric field patterning [95] Laser patterning [68] Resolution…”
Section: Methodsmentioning
confidence: 99%
“…Then, the LM pattern is directly drawn using magnetic field from a magnet on various substrates, as shown in Figure 13a. [92] This method is also effective for supermetallophobic substrates because the magnetic field enhances the adhesion of the pattern. The magnetic field patterning method does not require modification of the substrate, and can be performed on the surface of a curved, thin (e.g., egg shell, glass bottle, see Figure 13b), hard and soft substrates alike, solving the drawbacks of conventional LM patterning methods, which are mostly limited to planar elastomer substrates.…”
Section: Magnetic Field Guided Patterningmentioning
confidence: 99%
See 1 more Smart Citation
“…The dominant working principle of the liquid metal-based stretchable strain sensors is the geometrical effect. [167][168][169][170][171] In the following sections, it will be shown that the contribution of this mechanism to the overall sensing performance of nanomaterials-based stretchable sensors may not be significant.…”
Section: Geometrical Effectmentioning
confidence: 99%
“…Loading nickel particles also enables modulation of liquid metals by a magnetic field shown in the schematic of Figure 5d. [78] This image also shows a resulting patterned circuit from this process lighting up LEDs. This can be used to enable patterning of liquid metal on unique surface that ordinarily would not be wet by direct write.…”
Section: Magnetic Particle Fillersmentioning
confidence: 99%